a) $\dfrac{3}{2} - \left ( x - 2 \dfrac{1}{3} \right ) = \left | - \dfrac{3}{4} - \dfrac{1}{8} \right |$
$\dfrac{3}{2} - \left ( x - 2 \dfrac{1}{3} \right ) = \dfrac{7}{8} $
$- \left ( x - 2 \dfrac{1}{3} \right ) = \dfrac{7}{8} - \dfrac{3}{2}$
$- \left ( x - 2 \dfrac{1}{3} \right ) = - \dfrac{5}{8}$
$x - 2 \dfrac{1}{3} = \dfrac{5}{8}$
$x = \dfrac{5}{8} + 2 \dfrac{1}{3} $
b) $3 \times |4 \times x - 1| - 2 = 19$
$3 \times |4 \times x - 1| = 19+2$
$3 \times |4 \times x - 1| = 21$
$ |4 \times x - 1| = 21:3$
$|4 \times x - 1| = 7$
+ $4 \times x - 1 \geq 0 \Leftrightarrow x \geq \dfrac{1}{4}$ ta có: $|4x-1|=4x-1$, do đó:
$4x-1=7$
$x=.....$ (kết hợp đối chiếu điều kiện $x \geq \dfrac{1}{4}$)
+ $4 \times x - 1 < 0 \Leftrightarrow x < \dfrac{1}{4}$ ta có: $|4x-1|=1-4x$, do đó:
$1-4x=7$
$x=.....$ (kết hợp đối chiếu điều kiện $x < \dfrac{1}{4}$)